Perkawinan sebagai Perjanjian Kudus diperhadapkan dengan Pasangan Suami-Istri yang Belum Memiliki Anak dalam Perspektif Perjanjian Baru (International Forum of Researchers and Lecturers, 2025)
This article discusses the meaning of marriage as a holy covenant from the perspective of the New Testament, particularly for Christian couples who have not been blessed with children. This study employs a qualitative method through literature review of the Bible, theological books, and relevant scientific sources. The findings show that, in Christian teaching, the value of marriage is not solely determined by the presence of children, but rather by unity, love, and commitment centered on Christ. Marriage is seen as a reflection of the relationship between Christ and His church, requiring faithfulness and perseverance in facing life’s challenges, including the struggle of childlessness. New Testament theological principles provide comfort and strength for couples to remain faithful in marriage, and emphasize the importance of building a family that reflects God’s love and truth, regardless of having children.